Analisis Kerapuhan Seismik Struktur Gedung Tak Beraturan dengan Analisis Pushover - Hasyim, Wachid (Fakultas Teknik, Universitas Wiraraja, 2025)
Structural damage often occurs in buildings due to earthquake loads. Irregular buildings have a greater risk of damage due to earthquakes than regular buildings. Because the probability of an earthquake occurring in a structure cannot be predicted, an analysis is needed that can describe the vulnerability or fragility due to earthquakes. The purpose of this study was to determine the performance of irregular buildings and the probability of building damage based on seismic fragility. The method used to compile the seismic fragility curve is HAZUS, while the structural performance is obtained from the pushover analysis. Hazus is a method for estimating losses due to disasters, while the pushover analysis is in the form of a push-load application on the structure. Based on the results of the analysis, the structural performance point was obtained with a base shear force and displacement in the x direction of 4194.424 kN and 0.145 m, while in the y direction it was 4187.2016 kN and 0.152 m. The performance level of the building structure based on the analysis results is stated in the Damage Control (DC) condition according to ATC-40 and Life Safety (LS) according to FEMA 440. Based on the fragility curve, the probability of ultimate damage and yield conditions in moderate criteria and the probability of damage in the x and y directions of the building is 100%. The results of this study provide important information about the condition of irregular building structures during an earthquake so that it can be used for structural evaluation and mitigation during an earthquake.